2020
DOI: 10.29328/journal.ach.1001021
|View full text |Cite
|
Sign up to set email alerts
|

Silent cerebrovascular disease in hypertensive adults is frequent and age-dependent

Abstract: Background: Cerebral small vessel disease and extracranial atherosclerotic carotid disease are manifestations of silent cerebrovascular disease (CVD). Information on these two pathologies in hypertensive population with low cardiovascular risk (CVR) is scarce. Objective: To explore frequency and characteristics of silent CVD in hypertensive adults and cognitive repercussion of these alterations. Methods: 39 hypertensive patients (mean age: 53.5 years) were studied. Cerebral magnetic resonance imaging (3T), dop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Previous studies in Cuba had revealed that the proportion of subjects with low CV risk fluctuated between 59% and 86% in asymptomatic adults 23 24. With the revised WHO CV disease risk prediction charts, this proportion will undoubtedly change, considering that the cut-off for low CV risk has been set to <5%, instead of <10% as previously established 15.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Previous studies in Cuba had revealed that the proportion of subjects with low CV risk fluctuated between 59% and 86% in asymptomatic adults 23 24. With the revised WHO CV disease risk prediction charts, this proportion will undoubtedly change, considering that the cut-off for low CV risk has been set to <5%, instead of <10% as previously established 15.…”
Section: Discussionmentioning
confidence: 97%
“…A small investigation was recently conducted by us in 39 hypertensive patients, where CV risk was assessed with the PAHO CV risk calculator. 23 Although the MRI variables were not evaluated in the same manner, a high frequency of MRI lesions was encountered in patients with low to moderate CV risk, suggesting a limited association of brain parenchymal involvement with the level of CV risk.…”
Section: Revised Chartsmentioning
confidence: 99%